Estudo histológico, imunológico e parasitológico do tubo gastrointestinal de cães infectados com Leishmania (Leishmania) infantum chagasi - Maria Marta Figueredo (2013)
Gastrointestinal tract (GIT) disorders occur in dogs since 1980. Interestingly, we found a high parasite burden evident throughout the GIT mucosa, mainly in gross intestines in caecum and colon, but without severe lesions. It is known that in the vertebrate host GIT exerts local and systemic immunoregulatory response and it led us to consider whether Leishmania gains an advantage from this fact. The aim of this work was to better characterize the canine GIT pathology using histological, parasitological and immunological studies associated to the clinical status of the animals. Forty-four mongrel dogs naturally infected with Leishmania (Leishmania) infantum chagasi and obtained from the Control Zoonosis Center of the Municipality of Ribeirão das Neves, Belo Horizonte Metropolitan area, Minas Gerais (MG) state, Brazil, were analyzed. Other six uninfected dogs were used as controls. After necropsy, gross analysis were done without noticing any alterations, except the Peyers patches reactivity, localized mainly in ileum as white protuberant nodules in the wall (serosa). Under histological analysis, all infected dogs showed an increased number of cells in lamina propria (LP) expect in esophagus in comparison to controls. Macrophages, plasma cells and lymphocytes were the main cells with rare presence of neutrophils and eosinophils. Many of the macrophages showed a pale and abundant cytoplasm and less dense nucleus typical of epithelioid cells. Parasite distribution in the GIT was evident in all intestinal segments and layers of the intestinal wall (mucosal, muscular and submucosal) irrespective of the clinical status of the dogs. Interestingly, parasite distribution in the small intestine was diffuse through the LP, whereas in the large intestine it was concentrated near the muscularis and distant from the intestinal lumen. However, the parasite load was statistically higher in the caecum and colon than in other segments of the GIT. Some cellular antigens were analyses from cells obtained from LP of jejune and colon as: integrin CD11b and CD11c/CD18; the receptor of monocyte-macrophages CD14; receptors of macrophages and lymphocytes Toll type 2 (TLR2) and Type 9 (TLR9); receptors of macrophages mannose; CD4, CD8 and Foxp3 receptors of lymphocytes. In general, all studied receptors are high expressed in infected animals. We observed that expression of TLR2+ and CD11c+ as well as CD14+ Mannose+ was more frequent in the colon compared to the jejunum. Rather, TLR9+ was more frequent in the jejunum compared to the colon was also observed for CD11b+ and CD11b+ expressing CD14+, Mannose+, and TLR9+. T CD4+ e T CD4+/FOXP3+ was more frequent in jejune than colon. The CD8+ frequency was not different between jejune and colon, but different between jejune/colon in controls where in controls it was higher. However, infected animals revealed 27 increase CD4+ and Foxp3+ and decrease CD8+ frequencies. MFI (mean fluorescence intensity) was also carried out in cells of LP. There was difference between TLR9+, CD4+, CD8+, CD4+, FOXP3+ and CD11b+ whereas MFI was more intense in jejune. In contrast CD14+ and TLR2+ expression were more intense in colon. CD11c+ and Mannose+ did not present any MFI difference between jejune and colon. Frequency and IMF of T CD4+, CD8+ and Foxp3+ lymphocytes were analyzed in cervical and mesenteric lymph nodes. The positivity percentage of these receptors was different only related to controls. MFI was not different between lymph nodes. These results show that infected dogs have more CD4+ and Foxp3+, and less CD8+ antigen expression than uninfected dogs. Despite of the negative ELISA serum results for interleukin 4 (IL-4), interleukin 10 (IL-10) and tumoral necrotic factor-alpha (TNF-), in jejune we found IL-10 and TNF- where they are more intense than colon. Moreover, the cytokine IL-4 were mainly found in colon. Thus, the TGI segment with lower parasite load showed high frequency and expression of receptors CD4+, Foxp3+, CD11b+, TLR9+, besides the presence of IL-10 and TNF-. In contrast, the TGI segment with higher parasite load showed also concomitant high frequency of CD14, TLR2, CD11c and IL-4. We have concluded that in CVL there is a high Foxp3+ in the LP of the jejune. Probably the normal intestinal mucosa has an IL-10 dependent immunological mechanism where Foxp3+ cells are able to produce this IL-10. As Foxp3+ was also found in colon in normal conditions it suggests a local role of these cells in the intestinal homeostasis. Otherwise we must think that the integrity of the mucosa, both jejune and colon was preserve despite of the presence of parasites. Thus, this may led us to consider whether Leishmania gains an advantage from the intestinal immunoregulatory response (immunological tolerance). Such question will require further profound research and will help to elucidate the mechanisms underlying Leishmania infection.